Challenges in involvement of male spouse in family planning program in rural areas of Varanasi - Singh, Reema; Kumar, Alok; Kansal, Sangeeta (International Journal of Research in Medical Sciences, 2020)
Background: Globally, men have not shared equally with women the responsibility for fertility regulation. While family planning efforts have been directed almost toward women, the lack of male involvement may also reflect the limited options available to men. Current methods for men are condom, withdrawal, or permanent, such as vasectomy. The success of family planning depends on the involvement of couples but this hardly happen especially in rural areas. It is the belief, though erroneously among most males that the practice of family planning should be the sole responsibility of the female. The present study was a community based cross sectional study with the objective to assess challenges in involvement of male spouse in family planning program in rural areas. Methods: This is a community based and cross-sectional study was undertaken in randomly selected 4 villages of Kashi vidyapeeth block, Varanasi. Total enumeration of women from the selected villages delivered within last 3 years was done and their husbands were interviewed by using a pre-designed, pre-tested interview schedule. Chi-square test was applied to find out any association between the variables. P<0.05 was considered to be statistically significant, data was analyzed with statistical package for the social sciences (SPSS) 20 trial version. Results: These preliminary findings are part of thesis shows that out of 130 interviewed respondents, majority (89.5%) had aware about family planning and two third (66.2%) of the respondents said that either they or their wives are using family planning. More than half of the respondents were aware about male sterilization but none of them were using male sterilization. Majority (77.7%) of the respondents said that human immunodeficiency virus-acquired immune deficiency syndrome (HIV-AIDS) and 45.4% were said that sexually transmitted diseases or sexually transmitted infections (STDs/STIs) can be prevented by use of condom. More than half (53.8%) of the respondents were sole of the decision maker regarding the use of family planning. Conclusions: The present study concludes that the majority of the respondents were awareness about the family planning but practices of family planning is low in the study area. Health workers should educate the eligible couples for use of contraceptive methods. Promotion of male contraceptive usage should be done by intense awareness campaigns.